2000
DOI: 10.1172/jci6145
|View full text |Cite
|
Sign up to set email alerts
|

A selective inhibitor of the osteoclastic V-H+-ATPase prevents bone loss in both thyroparathyroidectomized and ovariectomized rats

Abstract: IntroductionInhibitors of bone resorption can preserve bone mass and maintain normal bone architecture, thereby preventing fractures in later life (1).The bone-resorption process requires secretion of protons by the osteoclasts (2). This allows the dissolution of the bone mineral and the maintenance of the acidic environment required by proteolytic enzymes to degrade the bone matrix (3). Protons are extruded by a proton pump belonging to the class of vacuolar-type H + -ATPases (V-H + -ATPases (4) that is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 40 publications
(29 reference statements)
1
72
0
Order By: Relevance
“…In the ADO patients, as well as other osteoclast-rich forms of osteopetrosis, it has been shown that bone formation is ongoing, despite the absence of bone resorption (11,17,41,42), a phenomenon that is also found in rodent models of osteoclast-rich osteopetrosis (70,71), and in animal models treated with inhibitors of osteoclastic acid secretion (63,72,73,74).…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 97%
“…In the ADO patients, as well as other osteoclast-rich forms of osteopetrosis, it has been shown that bone formation is ongoing, despite the absence of bone resorption (11,17,41,42), a phenomenon that is also found in rodent models of osteoclast-rich osteopetrosis (70,71), and in animal models treated with inhibitors of osteoclastic acid secretion (63,72,73,74).…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 97%
“…Osteoclast-selective PPIs may therefore be used as antiresorptive agents 12 with the potential of preventing fractures. [13][14][15][16] Administration of a selective inhibitor of the osteoclastic vacuolar H+/ K+ ATPase prevents bone loss in ovariectomized rats, an animal model representative of postmenopausal osteoporosis. 15 As bone resorption is necessary for the development of normal bone microstructure, however, one may speculate that PPI-induced blockade of the osteoclast-associated vacuolar proton pump may actually increase fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…(8) It has been reported that SB242784, a derivative of bafilomycin A1, had greater than 1000-fold selectivity for inhibition of osteoclast V-ATPase compared with V-ATPase measured in other tissues. (9) However, we could not confirm that SB242784 had any inhibitory selectivity for H + transport. The discrepancy may be attributed to a difference in the assay method.…”
Section: Discussionmentioning
confidence: 71%
“…The discrepancy may be attributed to a difference in the assay method. We measured H + transport activities of isolated membrane vesicles, whereas Visentin et al (9) measured total Mg + -dependent ATPase activities in individual cells using a histochemical technique. It is likely that their assay is inadequate to verify inhibitory selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation